The Effects of Health Belief Model Program on Knowledge, Stroke Prevention Behavior and Blood Pressure Levels in Hypertensive Patients The Responsibility Area of Kaeng Khro Hospital, Chaiyaphum Province - Hirungerd, Suptawee; Vutiso, Pitoon; Srimongkol, Maywadee (Journal of The Royal Thai Army Nurses, 2021)
The two groups Quasi-experimental design research was taken by pre-post measurement technique. The objectives were to study the effects of Health Belief Model Program on knowledge, stroke prevention behavior and blood pressure levels in hypertensive patients, located in the responsibility area of Kaeng Khro Hospital, Chaiyaphum province. Based on applied Health Belief Model mixed method with the concept of seven-colors Life Traffic Table Tennis and mobile phone follow-up. Samples were hypertensive patients with recruited by simple random sampling then assigned to be two groups, each group was 30 person. Proceeding from April to September of 2020. Collecting data by pre-post intervention questionnaire. Analyzing data by percentage, mean, standard deviation and t-test. Results found that post-intervention, the experimental group that received Health Belief Model Program had average knowledge, stroke prevention score higher than pre-intervention including average blood pressure level lesser than pre-intervention significantly (p-value <.05) Moreover, post-intervention, the experimental group that received Health Belief Model Program had average knowledge, stroke prevention score higher than pre-intervention including average blood pressure level lesser than pre-intervention significantly (p-value <.05) particular compared with the control group. Thus, conclusion support that Health Belief Model influencing the experimental group on knowledge, causation belief, symptoms of disease, self perception of exposure risk and more serious complication. Involved higher competency of stroke prevention behavior and enable reduced blood pressure level also.